High altitude, hypoxemic-induced responses in adult and fetal cerebral blood vessels - Longo, Lawrence D.; Pearce, William J. (Acta Andina, 2025)
In response to high altitude long-term hypoxemia, the cerebral arteries of adult and fetal sheep show decreased contractile responses to norepinephrine and other agonists. In this review we examine the pre-synaptic and post- synaptic contractile mechanisms which might account for these changes. In addition, we examine cerebral vessel relaxation and the role of pregnancy in altering these responses. The results highlight the profound differences in response of common carotid and intracranial arteries, as well as the significant differences in responses of fetus and adult. They also emphasize the role of high altitude, long-term hypoxemia in modulating pharmaco-mechanical coupling in the cerebrovasculature.